Systematic review: the impact of maternal pre-and postnatal cannabis use on the behavioral and emotional regulation in early childhood - Reyentanz, Emely; Gerlach, Jennifer; Kuitunen-Paul, Sören; Golub, Yulia (European Child & Adolescent Psychiatry, 2024)
Prenatal exposure to alcohol and tobacco has been associated with child regulatory abilities and problems, but less is known about the associations with cannabis exposure. This review seeks to address this gap primarily focusing on the effects of maternal cannabis use on the child. Thus, we investigate the association between pre- and postnatal cannabis exposure of the child and regulatory abilities and problems, as well as the underlying neurobiological mechanisms potentially mediating the associations. According to the PRISMA guidelines, a systematic literature review was performed based on a systematic literature search through Medline (PubMed), Web of Science and PsycInfo, including studies assessing children aged 0–6 years with cannabis exposure in the preconception, pre-or postnatal period (preconception, pre- and postnatal cannabis exposure [PCE]) and investigating child regulatory abilities, regulatory problems or neurobiological mechanisms. Of n = 1061 screened articles, n = 33 were finally included. Diminished regulatory abilities are more likely to be found in infants after PCE, while specific regulatory problems tend to be more frequently found after two years of age. Possible mechanisms are related to changes in methylation and expression of key genes involved in endocannabinoid, dopaminergic and opioid systems, increased cortisol reactivity and altered Secretory Immunoglobulin A levels. Furthermore, PCE has been associated with changes in brain structure and connectivity. Current findings indicate that PCE is associated with both age-dependent alterations in self-regulation and neurobiological changes in young children. However, evidence is limited due to the number of studies, small sample sizes and lack of control for maternal psychopathology. Longitudinal studies including psychometric data from mothers are needed in order to further understand the implications of PCE. Trial registration: The review is registered with PROSPERO (ID: CRD42023425115).
CRIS-Team Scopus Importer:2024-06-21
Keywords: Cannabis exposure; Early childhood; Neurobiological mechanisms; Self-regulation; Systematic review